METHODOLOGICAL FEATURES OF CREATING A SYSTEM OF INTERACTIVE TASKS OF INDEPENDENT WORK IN COMPUTER SCIENCE - Erekesheva, М.М.; Sagimbayeva, А.Е.; Kuzembayeva, А.Ж. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The purpose of the research presented in this article is the theoretical justification of the methodological features of creating a system of interactive tasks for the organization of independent work of students in school computer science. The article describes the methods used when creating software, the principle of choosing the environment used, and the stages of creation. The object of research is the development of an interactive system of tasks for independent work in computer science. Research methods - theoretical methods - literature search, collection and application of material, empirical methods - observation, interview, survey, pedagogical experiment and statistical processing of experiment results, web application design, technology creation, OBP methods. As a result of the study, the necessity of creating an interactive system of tasks for organizing independent work of students in computer science was substantiated, didactic requirements were specified, means of creating an interactive system of tasks were determined, a web portal was created, consisting of a set of interactive tasks for organizing independent work of students in learning the division "Programming algorithms for jazyke Python".